THE ANALYSIS OF THE CORRELATION BETWEEN THE EVOLUTION OF THE GDP AND THAT OF THE CAPITAL AND LABOUR FACTORS IN ROMANIA - Gheorghe ZAMAN; Zizi GOSCHIN; Claudiu HERTELIU (Revista Romana de Economie, 2005)
Researching the correlation between GDP and production factors has been performed based on several procedures and quantitative-qualitative techniques, so as to underpin hierarchies and provision the factors’ contribution to GDP. Our study approaches first the dynamic correlation between GDP and gross formation of fixed capital, based on using the ICOR (incremental capital output ratio) indicator, with and without time lag, in four computation variants and thereafter the relation between GDP and the capital and labour production factors with the help of the production functions of the type Cobb-Douglas. Both directions of analysis have been finalised with prognosis computations with respect to investment needs in order to ensure a certain growth of GDP for the future.